Domesticity and power in the early Mughal world - Lal, Ruby (Cambridge studies in Islamic civilization., 2005)
Ruby Lal explores domestic life and the place of women in the Mughal court of the sixteenth century. Challenging traditional, orientalist interpretations of the haram that have portrayed a domestic world of seclusion and sexual exploitation, she reveals a complex society where noble men and women negotiated their everyday life and public-political affairs.